Estimating Real Production and Expenditures across Nations: A Proposal for Improving the Penn World Tables - Feenstra, Robert C; Heston, Alan; Timmer, Marcel P; Deng, Haiyan (The Review of Economics and Statistics, 2009)
We propose a new approach to the international comparison of real GDP, as measured from the output-side. The traditional Gary-Khamis system, which measures real GDP from the expenditure-side, is modified to include differences in the terms of trade between countries. It is shown that this system has a strictly positive solution under mild assumptions. On the basis of a sample of 151 countries in 1996, it is shown that differences between real GDP measured from the expenditure-side and output-side can be substantial, especially for small open economies. We also obtain cross-country measures of “real openness” and the terms of trade.